Tigecycline plus Standard Therapy is More Effective than Standard Therapy Alone for Treating Infections in Febrile Neutropenic Cancer Patients - Butterman, Eric (MD Conference Express, 2011)
Tigecycline, first in a new class of glycylcyclines, in combination with piperacillin/tazobactam, is effective, safe, and well tolerated in high-risk febrile neutropenic oncohematologic patients. This combination therapy may aid in reducing the increase and extensive use of carbapenems, which have been associated with an increase in multidrug-resistant bacteria.